Function of carbohydrate recognition by C-type lectins on dendritic cells in “host defence” and “immune homeostasis” - Van Kooyk, Yvette (Henry Stewart Talks, 2013)
Function of Carbohydrate Recognition by C-type Lectins on Dendritic Cells in “Host Defense” and “Immune Homeostasis", Dendritic cells in innate and adaptive immunity, Viral defense by mucosal dendritic cells, Inhibitors of DC-SIGN block virus binding and cellular function, The C-type lectin DC-SIGN, Common classes of mammalian glycans, DC-SIGN receptor for HIV-1 and Hepatitis C virus on DC, Langerhans cells, LC protects us against infection with HIV-1, How are bacteria recognized by the human immune system?, Pathogen-associated molecular patterns, Toll-like receptors, TLRs and C-type lectins, Antigen presentation by C-type lectins, Glycan specificity of the C-type lectins, Orchestrating adaptive immune responses by pathogen recognition, Helicobacter pylori, Mycobacterium tuberculosis, DC-SIGN enhances TLR-induced IL-10 responses, Pathogens target DC-SIGN to modulate immune responses, C-type lectins (DC-SIGN) in bacterial infections, C-type lectin function, DCs interact with neutrophils through DC-SIGN, Glycan changes associated with cancer